Poultry Litter Feeding Ban: Implications of the 2nd Interim Rule for Animal Feeding - Matt Hersom; Dale Dubberly; Kelly Friend (EDIS)
On January 26, 2004, the FDA issued four interim rules as a result of the first confirmed case of Bovine Spongiform Encephalopathy (BSE) in cattle in the United States. The 2nd interim rule simply stated “will also ban the use of poultry litter as a feed ingredient for ruminant animals.” Issuance of this interim rule has raised concerns in the Florida poultry industry concerning disposal of the poultry litter by-product and in the Florida cattle industry concerning the loss of a low-cost alternative feed source. This document is AN150, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. Published May 2004.